The Antinociceptive Responses of MTDZ to Paclitaxel−Induced Peripheral Neuropathy and Acute Nociception in Mice: Behavioral, Pharmacological, and Biochemical Approaches - Ketlyn P. da Motta; Carolina C. Martins; Vanessa M. Macedo; Beatriz F. dos Santos; Nelson Luís De C. Domingues; Cristiane Luchese; Ethel A. Wilhelm (Pharmaceuticals, 2023)
The efficacy of 5-((4-methoxyphenyl)thio)benzo[c][1,2,5] thiodiazole (MTDZ) in mitigating paclitaxel (PTX)-induced peripheral neuropathy was investigated in male and female Swiss mice. The study examined the effects of MTDZ on various pathways, including transient receptor potential cation channel subfamily V member 1 (TRPV1), glutamatergic, nitrergic, guanylate cyclase (cGMP), serotonergic, and opioidergic. Mice received intraperitoneal PTX (2 mg/kg) or vehicle on days 1, 2, and 3, followed by oral MTDZ (1 mg/kg) or vehicle from days 3 to 14. Mechanical and thermal sensitivities were assessed using Von Frey and hot plate tests on days 8, 11, and 14. The open field test evaluated locomotion and exploration on day 12. On day 15, nitrite and nitrate (NOx) levels and Ca2+−ATPase activity in the cerebral cortex and spinal cord were measured after euthanizing the animals. MTDZ administration reversed the heightened mechanical and thermal sensitivities induced by PTX in male and female mice without affecting locomotion or exploration. MTDZ also modulated multiple pathways, including glutamatergic, NO/L−arginine/cGMP, serotonergic (5−HT1A/1B), opioid, and TRPV1 pathways. Additionally, MTDZ reduced NOx levels and modulated Ca2+−ATPase activity. In conclusion, MTDZ effectively alleviated PTX−induced peripheral neuropathy and demonstrated multi-targeted modulation of pain-related pathways. Its ability to modulate multiple pathways, reduce NOx levels, and modulate Ca2+−ATPase activity makes it a potential pharmacological candidate for peripheral neuropathy, acute nociceptive, and inflammatory conditions. Further research is needed to explore its therapeutic potential in these areas.